Alternatif Profesi Melalui Pembelajaran Eektif - Suyanto Suyanto (Institut Seni Indonesia Surakarta, 2006)
Indonesia has many variety handycraft, which can evaluate from media ( wood, metal, leather, rattan paper, bamboo, stone, rock, etc), technique and process (example ceramic, textile, batik, songket weave, embroidery, weave, etc). Handicraft art products are aimed in many forms and style to fulfill a lot of necessity and function of life, from Sabang till Merauke spread out Indonesia handicrafts harmony the map of artistic national culture.Keyword: handicraft, national culture